International Market Selection model using newly developed geometric International Market Selection Space - Mazlan Hussein,; Azman Hassan,; Wan Azman Saini Wan Ngah,; Raja Nerina Raja Yusof,; Khairil Wahidin Awang, (Penerbit Universiti Kebangsaan Malaysia, 2019)
International Market Selection (IMS) is literally a process in identifying and selecting feasible international market opportunities for exporting. It is a methodological process whereby suitable variables are vetted through a model in order to produce output in the form of processed information that would help export marketers in decision-making. The new IMS model, introduced as Geometric International Market Selection Space (GIMSS), rooted from the Trade Intensity Index (TI) Index and Geometric Trade Intensity Space Box (GTISB) is proposed as a complimentary tool to be used by international marketers. The constructed GIMSS model utilises both trade elements (exports and imports) with no filtering and weighting processes, employs changes within changes measurement, embeds quality perspective measurement as alternative game changer in identifying International Export Opportunities (IEO), and able to do future projection of IEO. In addition, even though this GIMSS model does not have weighting scheme, it can still perform trade-off process between volume and quality elements. The GIMSS is capable of identifying and categorising the host country market potential into low, intermediate or high market potential at product level. With that policy maker would be able to employ this information conjointly with competitive index of exporting country and make assessment in the perspective of cross checking between host country market potential levels with exporting country competitive advantage status.